2014
DOI: 10.4317/medoral.19518
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of Naproxen, Etodolac and Diclofenac on postoperative sequelsfollowing third molar surgery: A randomised, double-blind, crossover study

Abstract: Objectives: To compare the three non-steroidal anti-inflammatory agents (NSAIDs) diclofenac potassium, etodolac and naproxen sodium in relation to pain, swelling and trismus following impacted third molar surgery. Study Design: The study was a randomized and a double-blinded study which included 42 healthy young individuals with impacted third molars and bone retention. Patients were randomly assigned to 3 groups (n: 14) to which diclofenac potassium, naproxen sodium and etodolac were administered orally an ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 26 publications
0
27
0
8
Order By: Relevance
“…Third molar extraction is the most common surgical procedure in dentistry, and it is commonly used to investigate acute postoperative pain and inflammation (1). In particular, third molar surgery involves the manipulation of the molar and the surrounding soft tissue and bone.…”
Section: Introductionmentioning
confidence: 99%
“…Third molar extraction is the most common surgical procedure in dentistry, and it is commonly used to investigate acute postoperative pain and inflammation (1). In particular, third molar surgery involves the manipulation of the molar and the surrounding soft tissue and bone.…”
Section: Introductionmentioning
confidence: 99%
“…11 One study compared the preoperative administration of oral diclofenac potassium, etodolac, and naproxen sodium on postoperative pain, swelling, and trismus. 12 The study concluded that diclofenac potassium was best at reducing swelling and equal to naproxen sodium and etodolac in reduction of pain and trismus. In another study, dexketoprofen trometamol was used in an intravenous preparation preoperatively and was found to have an excellent preemptive decrease in pain and swelling caused by third molar surgery.…”
Section: Nonsteroidal Antiinflammatory Drugs and Postoperative Pain Cmentioning
confidence: 99%
“…It is comparable with etodolac, but less effective in swelling when compared with diclofenac when they were used in oral surgical procedures, including postoperative third molar surgery or orthodontic pain [96][97][98]. Diclofenac is used in moderate to severe pain following third molar extraction and it could be used in an intravenous form in risk population groups such as the elderly and renal insufficiency, postoperative anticoagulation which uses ketorolac as the only choice for the moderate to severe acute pain.…”
Section: Analgesic Monotherapy Versus Combined Therapy In Dental Pracmentioning
confidence: 99%